Mass spectrometry provides accurate characterization of two genetic marker types in Bacillus anthracis. (October 2004) - Ert, Matthew N. Van; Hofstadler, Steven A.; Jiang, Yun; Busch, Joseph D.; Wagner, David M.; Drader, Jared J.; Ecker, David J.; Hannis, James C.; Huynh, Lynn Y.; Schupp, James M.; Simonson, Tatum S.; Keim, Paul
Epidemiological and forensic analyses of bioterrorism events involving Bacillus anthracis could be improved if both variable number tandem repeats (VNTRs) and single nucleotide polymorphisms (SNPs) could be combined on a single analysis platform. Here we present the use of electrospray ionization Fourier transform ion cyclotron resonance mass spectrometry (ESI-FTICR-MS) to characterize 24 alleles from 6 VNTR loci and 11 alleles from 7 SNP loci in B. anthracis . The results obtained with ESI-FTICRMS were consistent with independent results obtained from traditional approaches using electrophoretic detection of fluorescent products. However, ESI-FTICR-MS improves on the traditional approaches because it does not require fluorescent labeling of PCR products, minimizes post-PCR processing, obviates electrophoresis, and provides unambiguous base composition of both SNP and VNTR PCR products. In addition, ESI-FTICR-MS allows both marker types to be examined simultaneously and at a rate of approximately 1 sample per min. This technology represents a significant advance in our ability to rapidly characterize B. anthracis isolates using VNTR and SNP loci.